2011
DOI: 10.1038/hr.2011.112
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CYP3A5 polymorphism (6986G>A) with blood pressure and hypertension

Abstract: The cytochrome P450 family 3 subfamily A polypeptide 5 (CYP3A5) gene has been implicated in the regulation of blood pressure (BP) and thus, may serve as a potential risk factor for the development of hypertension. However, current results regarding the association between CYP3A5 single nucleotide polymorphisms and BP/hypertension have been inconsistent. In this study, we performed a meta-analysis to evaluate the association between the CYP3A5 rs776746 (6986G4A) polymorphism and BP/hypertension. Ten studies (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…A meta-analysis suggested that, although there was no overall effect of CYP3A5 expressor status on BP or hypertension, in white populations, the carriers of functional CYP3A5*1 allele had lower systolic BP compared with noncarriers. 47 In addition to CYP3A4, the polymorphic CYP3A5 enzyme is involved in the synthesis of 4βHC 9 and the concentration of 4βHC increases stepwise with the number of CYP3A5*1 alleles present. 9 Thus, as CYP3A5*1 carriers have higher circulating 4βHC concentration than CYP3A5 nonexpressors, 9 this would be consistent with our finding that higher 4βHC is associated with lower 24-hour BP.…”
Section: Articlementioning
confidence: 99%
“…A meta-analysis suggested that, although there was no overall effect of CYP3A5 expressor status on BP or hypertension, in white populations, the carriers of functional CYP3A5*1 allele had lower systolic BP compared with noncarriers. 47 In addition to CYP3A4, the polymorphic CYP3A5 enzyme is involved in the synthesis of 4βHC 9 and the concentration of 4βHC increases stepwise with the number of CYP3A5*1 alleles present. 9 Thus, as CYP3A5*1 carriers have higher circulating 4βHC concentration than CYP3A5 nonexpressors, 9 this would be consistent with our finding that higher 4βHC is associated with lower 24-hour BP.…”
Section: Articlementioning
confidence: 99%
“…Studies showing an association of the * 1 allele with higher blood pressure or with hypertension have all been carried out in individuals of African descent or in older White individuals [49]. In a recent meta-analysis (for hypertension: 10 studies including more than 9500 individuals, and for blood pressure: 12 studies including more than 9000 individuals), no association was found overall with the CYP3A5 genotype, and, in Whites, a modest association was observed between * 1 and lower systolic blood pressure [50]. …”
Section: Variant-disease Associationsmentioning
confidence: 99%
“…The cytochrome P450 family 3, subfamily A, member 5 ( CYP3A5 ) gene on chromosome 7 encodes an enzyme of the cytochrome P450 family, mostly expressed in the liver, which is involved in the metabolism of a large variety of drugs and the synthesis of cholesterol and other lipids. 38 CYP3A5 is known to be involved in the development of essential hypertension in humans 39 and to influence the required dose of the calcineurin inhibitors cyclosporin and tacrolimus in solid organ transplantation recipients. The rs776746 G allele is a loss-of-function allele, which disrupts a splice site.…”
Section: Discussionmentioning
confidence: 99%